Alex Delaware: Compulsion - Book 22 - Kellerman, Jonathan (New York : Ballantine Books, 2008)
Baffled by a serial killer who uses disguises to claim his victims, LAPD Detective Milo Sturgis teams up with criminal psychologist Alex Delaware to track down one of the most ingenious and ruthless monsters they have ever faced.
Keywords: Fiction; Thriller